Gender and conversational interaction - edited by Deborah Tannen (Oxford University Press, 1993)
Go get ya a French! : romantic and sexual teasing among adolescent girls / Donna Eder -- Cooperative competition in adolescent "girl talk" / Penelope Eckert -- Community and contest : midwestern men and women creating their worlds in conversational storytelling / Barbara Johnstone -- Pickle fights : gendered talk in preschool disputes / Amy Sheldon -- Tactical uses of stories : participation frameworks within boys' and girls' disputes / Marjorie Harness Goodwin -- Gender, politeness, and confrontation in Tenejapa / Penelope Brown -- The relativity of linguistic strategies / Deborah Tannen -- Who's got the floor? / Carole Edelsky -- Women, men, and interruptions : a critical review / Deborah James and Sandra Clarke -- Understanding gender differences in amount of talk : a critical review of research / Deborah James and Janice Drakich.